Development of Family Based Food Security Policy Program Evaluation Model in The Sustainable Food Yard (P2l) Program in Tuban District - Pipin Diah Larasati; Agus Sukristyanto; Rachmawati Novaria (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
Increasing public knowledge and information about the diversity of food consumption is expected to reduce people's dependence on rice as a staple food, which is still high, improve diet so that it is more diverse, nutritionally balanced and safe which supports the community to be able to live a healthy, active and more productive life. productive. This study aims to evaluate the implementation of Yard Land Utilization Optimization activities in Tuban Regency in the Sustainable Food Yard (P2L) activity program, and Women Farmer Groups (KWT) in 2021 in Tuban district. A descriptive qualitative approach is used as an approach to obtain a more detailed review of the evaluation that implies the CIPP concept. The results of the research can explain and construct the CIPP evaluation model, that CIPP in the context aspect is able to describe things that need to be considered in program planning such as environmental characteristics and farming communities, especially women farmers, curriculum, strengths and weaknesses of implementing staff, facilities and infrastructure, funding, and the P2L and KWT communities; Evaluation of inputs to activities is able to identify and assess (1) the methods used in the food cultivation and food diversification program, (2) strategies to achieve the goals of the home yard utilization program, and (3) the design of the selected strategy implementation; in process evaluation it is known the pattern of relationship between executors and women farmers and the community, communication media, logistics, required resources, schedule of activities, and potential causes of program failures; while product evaluation produces information to determine to what extent predetermined goals can be achieved and to determine whether the strategy and achievement of goals, namely diversification and family-based food security, are sufficient, the impact of the program on targets.